Transit in Regional Economic Development: The Case of the Kaliningrad Exclave - Voloshenko, Ksenia Yu.; Gumenyuk, Ivan S.; Arne Roos, Nils Göran (European Spatial Research and Policy, 2020)
The study analyses the role of the transit function in the development of a regional transport system drawing on the example of the Kaliningrad exclave region (Russia). The article studies the role and extent of the impact of changes in the volume and structure of transit operations on the value-added creation in the regional economy. The assessment of the transit function was conducted using analytical software for strategizing and situational forecasting of the socio-economic development of the Kaliningrad region, the analogue of which is the CGE-model. The article describes the results of the regional value-added modelling based on the integrated index of gross regional product (GRP) and the changing volume and structure of transit cargo. The article explores the transit specialisation options for the Kaliningrad region based on different scenarios of its social and economic development and the changes in external factors. The results can be applied to similar studies on assessing the transit potential of a particular territory and developing measures to support the transportation system development in other regions.